A current collector and its preparation method and application
By depositing a conductive metal layer on the liquid crystal polymer modified fiber cloth to form a porous current collector, the problem of high-temperature thermal shrinkage of the metal foil current collector in lithium-ion batteries is solved, and the safety and energy density of the battery are improved.
Patent Information
- Application Number
- CN202210510141.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-05-11
AI Technical Summary
The metal foil current collector of existing lithium-ion batteries is prone to heat shrinkage at high temperatures, resulting in safety problems. At the same time, the thickness and mass of the metal foil per unit area are relatively large, which affects the energy density of the battery.
A liquid crystal polymer modified fiber cloth with a porous structure is used as the substrate for the current collector, and a conductive metal layer is deposited on its surface and porous structure to form a current collector of the liquid crystal polymer modified fiber cloth substrate with a porous structure and a current collector of the conductive metal layer.
By embedding active materials into the current collector pores, the content of active substances per unit volume is increased, the risk of metal lithium precipitation is reduced, the possibility of internal short circuit is reduced, and the safety and energy density of the battery are improved.
Smart Images

Figure CN114824283B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a current collector and a preparation method and application thereof. Background Art
[0002] At present, the electrode sheets of lithium-ion batteries mainly adopt a layered stacking mode of coating electrode materials on metal foil current collectors. Since the metal foil current collector and the electrode material layer are completely separated, the contact between the two layers forms a large interface resistance. Improving the surface contact between the metal foil current collector and the electrode material layer has become one of the key issues in making high-energy-density batteries.
[0003] The traditional positive electrode current collector uses aluminum foil with a thickness of 15 to 20 μm, and the negative electrode current collector uses copper foil with a thickness of 8 to 12 μm. Metal foil has good electrical conductivity, but its mechanical processing performance is poor at the above thickness, which shows that it is overall brittle and lacks toughness. Once it is impacted or deformed by external force, it will produce irreversible marks or even holes, causing leakage current in the positive and negative electrodes of the battery, which not only affects the performance efficiency of the entire battery, but may even cause serious safety problems. In addition, the unit area mass of metal foil is large. Traditional copper foil and aluminum foil account for 15 to 20% of the total battery mass, which is the heaviest part of the battery except for the positive and negative electrode materials, which will lead to a decrease in the battery energy density.
[0004] In response to the above problems, a Chinese patent with publication number CN106898729A discloses a current collector with a textile substrate of a polymer matrix as a substrate. The current collector has a small mass per unit area and can effectively improve the volume energy density of the battery. However, the polymer matrix will shrink under high temperature conditions (170-200°C), which will eventually lead to safety problems of the battery. Summary of the invention
[0005] The object of the present invention is to provide a current collector and a preparation method and application thereof, wherein the current collector can effectively solve the safety problem caused by high-temperature thermal shrinkage of a polymer substrate and can also improve the volume energy density of a lithium-ion battery.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a current collector, comprising a liquid crystal polymer modified fiber cloth substrate with a porous structure and a conductive metal layer attached to the surface of the liquid crystal polymer modified fiber cloth substrate with a porous structure and in the pore structure.
[0008] Preferably, the liquid crystal polymer modified fiber cloth substrate with a porous structure has a thickness of 4 to 70 μm, a porosity of 10 to 60%, an operating temperature of -60 to 350° C., a tensile strength of 1 to 1500 MPa, and a pore size of 0.01 to 60 μm.
[0009] Preferably, the liquid crystal polymer modified fiber cloth substrate having a porous structure includes a liquid crystal polymer non-woven fabric or a porous liquid crystal polymer film.
[0010] Preferably, the thickness of the conductive metal layer is 0.1 to 10 μm;
[0011] The number of the conductive metal layers is ≥1.
[0012] Preferably, the material of the conductive metal layer includes one or more of Ni, Cu, Ag, Au, Al, Sn, metal oxides and alloys;
[0013] The metal elements of the alloy include two or more of Ni, Cu, Ag, Au, Al and Sn;
[0014] The metal elements in the metal oxide include one or more of Ni, Cu, Ag, Au, Al and Sn.
[0015] The present invention also provides a method for preparing the current collector described in the above technical solution, comprising the following steps:
[0016] A conductive metal layer is deposited on the surface and pore structure of a liquid crystal polymer modified fiber cloth substrate with a porous structure to obtain a current collector.
[0017] Preferably, the deposition method is chemical plating, electroplating, evaporation or magnetron sputtering.
[0018] Preferably, when the deposition method is chemical plating, the chemical plating solution used is alkaline;
[0019] The chemical plating solution comprises a soluble metal salt, a reducing agent, a complexing agent and a stabilizer.
[0020] Preferably, the reducing agent is formaldehyde; the complexing agent is a mixture of sodium tartrate and disodium EDTA; and the stabilizer is thiourea.
[0021] The present invention also provides the use of the current collector described in the above technical solution or the current collector prepared by the preparation method described in the above technical solution in a lithium ion battery.
[0022] The present invention provides a current collector, comprising a liquid crystal polymer modified fiber cloth substrate with a porous structure and a conductive metal layer attached to the surface of the liquid crystal polymer modified fiber cloth substrate with a porous structure and in the pore structure. The present invention uses the liquid crystal polymer modified fiber cloth substrate with a porous structure as the base of the current collector, so that the active material (conductive metal) can be embedded in the pores of the current collector, and the active materials can be interconnected on both sides of the current collector, which not only increases the content of active materials per unit volume, but also enables lithium ions to shuttle between the two sides of the pole piece, thereby reducing the bellows of metal lithium precipitation, reducing the risk of internal short circuit, and thus improving safety; and the liquid crystal polymer material in the liquid crystal polymer modified fiber cloth substrate with a porous structure itself has the characteristic of high temperature resistance, and when it is used as a current collector, it can also alleviate the problem of thermal shrinkage caused by excessively high operating temperature, thereby improving the safety of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a physical picture of the current collector described in Example 1 of the present invention;
[0024] Figure 2 It is a high-power microscope structure of the current collector described in Example 1 of the present invention;
[0025] Figure 3 This is a scanning electron microscope structure of the current collector described in Example 1 of the present invention;
[0026] Figure 4 This is the scanning electron microscope structure of the current collector described in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The present invention provides a current collector, comprising a liquid crystal polymer modified fiber cloth substrate with a porous structure and a conductive metal layer attached to the surface of the liquid crystal polymer modified fiber cloth substrate with a porous structure and in the pore structure.
[0028] In the present invention, the thickness of the liquid crystal polymer modified fiber cloth substrate with a porous structure is preferably 4 to 70 μm, more preferably 10 to 60 μm, and most preferably 30 to 50 μm; the porosity is preferably 10 to 60%, and most preferably 20 to 40%; the operating temperature is preferably -60 to 350°C; the tensile strength is preferably 1 to 1500 MPa, more preferably 5 to 1000 MPa, and most preferably 30 to 600 MPa; the pore size is preferably 0.01 to 60 μm, and more preferably 0.01 to 50 μm. In the present invention, the volume of gas vertically passing through the liquid crystal polymer modified fiber cloth substrate with a porous structure per unit time per unit area is used to characterize the porosity of the liquid crystal polymer modified fiber cloth substrate with a porous structure, and the porosity of the liquid crystal polymer modified fiber cloth substrate with a porous structure is preferably 5 to 1000 cc / cm 2 / sec, more preferably 10 to 500 cc / cm2 / sec, most preferably 30 to 300cc / cm 2 In the present invention, the "operating temperature" can be understood as the temperature range within which the liquid crystal polymer modified fiber cloth substrate with a porous structure can maintain stable performance.
[0029] In the present invention, the liquid crystal polymer modified fiber cloth substrate with a porous structure preferably includes a liquid crystal polymer non-woven fabric or a porous liquid crystal polymer film, more preferably the Vecrus series of Kuraray Co., Ltd. of Japan, and the brand is preferably MBBK4F-F, MBBK6F-F.
[0030] In the present invention, the thickness of the conductive metal layer is preferably 0.1 to 10 μm, more preferably 0.1 to 5 μm.
[0031] In the present invention, the number of the conductive metal layers is preferably ≥1, more preferably 1 or 2.
[0032] In the present invention, the material of the conductive metal layer preferably includes one or more of Ni, Cu, Ag, Au, Al, Sn, metal oxides and alloys; the metal elements of the alloy preferably include two or more of Ni, Cu, Ag, Au, Al and Sn; the metal elements in the metal oxide preferably include one or more of Ni, Cu, Ag, Au, Al and Sn; the present invention does not have any special limitation on the ratio of the metal elements in the alloy, and the ratios well known to those skilled in the art can be adopted.
[0033] The present invention also provides a method for preparing the current collector described in the above technical solution, comprising the following steps:
[0034] A conductive metal layer is deposited on the surface and pore structure of a liquid crystal polymer modified fiber cloth substrate with a porous structure to obtain a current collector.
[0035] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0036] Before deposition, the present invention preferably pre-treats the liquid crystal polymer modified fiber cloth substrate having a porous structure, and the pre-treatment preferably includes degreasing, roughening and activation in sequence; the present invention does not have any special restrictions on the degreasing and roughening process, and can be carried out using a process well known to those skilled in the art. In the present invention, the activation solution used in the activation is preferably a colloidal palladium activation solution.
[0037] In the present invention, the preparation process of the colloidal palladium activation solution preferably includes:
[0038] Mix 100 mL of hydrochloric acid (analytical grade) and 200 mL of deionized water, stir evenly, then add 1 g of palladium chloride and stir, then add 2.53 g of stannous chloride and stir to allow it to react and dissolve for 12 minutes at 32°C to obtain solution A;
[0039] Add 75 g of tin chloride to 200 mL of hydrochloric acid (analytical grade), stir until completely dissolved, then add 7 g of sodium stannate to make a white emulsion to obtain solution B;
[0040] The B solution was slowly poured into the A solution, and diluted to 1000 mL with deionized water to obtain the colloidal palladium activation solution.
[0041] In the present invention, the activation temperature is preferably 23° C., and the activation time is preferably 2 min.
[0042] In the present invention, the deposition method is preferably chemical plating, electroplating, evaporation or magnetron sputtering.
[0043] When the deposition method is chemical plating, the chemical plating solution used in the chemical plating is preferably alkaline, and the pH value is preferably ≥9, more preferably 10-11. In the present invention, the pH value of the chemical plating solution is preferably adjusted by sodium hydroxide as a pH regulator. In the present invention, the chemical plating solution preferably includes a soluble metal salt, a reducing agent, a complexing agent and a stabilizer. The present invention does not have any special restrictions on the type of the soluble metal salt, and the type familiar to those skilled in the art can be used. In the present invention, the reducing agent is preferably formaldehyde; the complexing agent is preferably a mixture of sodium tartrate and disodium EDTA, and the mass ratio of sodium tartrate and disodium EDTA is preferably (1-2):1, more preferably 1.3:1; the stabilizer is preferably thiourea. In the present invention, the concentration of the soluble metal salt in the chemical plating solution is preferably 1-10 g / L, more preferably 4-8 g / L, and most preferably 6 g / L; the concentration of the reducing agent in the chemical plating solution is preferably 1-15 g / L, more preferably 5-10 g / L, and most preferably 8.5 g / L; the concentration of the complexing agent in the chemical plating solution is preferably 2-10 g / L, more preferably 4-7 g / L, and most preferably 5 g / L; the concentration of the stabilizer in the chemical plating solution is preferably 0.01-0.1 g / L, more preferably 0.02-0.07 g / L, and most preferably 0.041 g / L.
[0044] In the present invention, the temperature of the chemical plating is preferably 35 to 90° C., more preferably 45 to 70° C., and most preferably 60° C.; the time is preferably 20 to 80 min, and more preferably 30 to 60 min.
[0045] After the chemical plating is completed, the present invention also preferably includes washing and drying in sequence; the washing is preferably performed with deionized water; the present invention has no special limitation on the drying process, and the drying process can be performed using a process well known to those skilled in the art. In a specific embodiment of the present invention, the drying is performed under hot pressing conditions of 75°C and 2 kg / square inch.
[0046] The present invention has no special limitation on the electroplating, evaporation or magnetron sputtering process, and the process well known to those skilled in the art can be used.
[0047] The present invention also provides the use of the current collector described in the above technical solution or the current collector prepared by the preparation method described in the above technical solution in a lithium ion battery.
[0048] The method of application in the present invention preferably includes:
[0049] Coating a negative electrode active material on the surface of the current collector to obtain a negative electrode sheet;
[0050] A lithium-ion battery is assembled using the negative electrode sheet as the negative electrode.
[0051] The present invention does not have any special limitation on the negative electrode material, and any type familiar to those skilled in the art may be used.
[0052] When assembling a lithium-ion battery, the present invention does not have any special restrictions on the positive electrode and the electrolyte, and those known to those skilled in the art can be used.
[0053] The current collector provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0054] Embodiments 1 to 4
[0055] Liquid crystal polymer nonwoven fabrics of the Vecrus series of Kuraray Co., Ltd., with the brands MBBK4F-F (Example 1) and MBBK6F-F (Examples 2 to 4), were subjected to degreasing, roughening and activation in sequence to obtain pretreated liquid crystal polymer (LCP) nonwoven fabrics;
[0056] The liquid crystal polymer nonwoven fabric is placed in a chemical plating solution (comprising 6 g / L of anhydrous copper sulfate, 8.5 g / L of formaldehyde, 5 g / L of a complexing agent (sodium tartrate and disodium EDTA in a mass ratio of 1.3:1), 0.041 g / L of thiourea, and sodium hydroxide is used as a pH regulator to adjust the pH value of the chemical plating solution to 11), chemically plated at 60° C. for 1 min, washed with deionized water, taken out and dried under hot pressing conditions of 75° C. and 2 kg / square inch to obtain a current collector (metallized polymer-based nonwoven fabric);
[0057] Example 5
[0058] The Vecrus series of Kuraray Co., Ltd. of Japan, with the brand name MBBK4F-F, uses a conventional vacuum magnetron sputtering process to plate a layer of nickel metal on the surface of the non-woven fabric with a thickness of 0.1um;
[0059] The liquid crystal polymer nonwoven fabric is placed in an aqueous electroplating solution containing 70 g / L copper pyrophosphate, 300 g / L potassium pyrophosphate, 15 g / L citric acid and 3 ml / L ammonia water. The pH is adjusted to about 7.5 with sulfuric acid. After electroplating at 50°C for 1 min, the fabric is washed with deionized water, taken out and dried under hot pressing conditions at 75°C and 2 kg / square inch to obtain a current collector (metallized polymer-based nonwoven fabric).
[0060] Example 6
[0061] The Vecrus series of Kuraray Co., Ltd. of Japan, with the brand name MBBK4F-F, uses conventional vacuum evaporation plating technology to plate a layer of nickel metal on the surface of the non-woven fabric with a thickness of 0.1um;
[0062] The liquid crystal polymer nonwoven fabric is placed in an aqueous electroplating solution containing 70 g / L copper pyrophosphate, 300 g / L potassium pyrophosphate, 15 g / L citric acid and 3 ml / L ammonia water. The pH is adjusted to about 7.5 with sulfuric acid. After electroplating at 50°C for 1 min, the fabric is washed with deionized water, taken out and dried under hot pressing conditions of 75 degrees and 2 kg / square inch to obtain a current collector (metallized polymer-based nonwoven fabric).
[0063] The structural parameters of the current collectors prepared in Examples 1 to 6 are shown in Table 1:
[0064] Table 1 Structural parameters of the current collectors prepared in Examples 1 to 6
[0065]
[0066]
[0067] Test Case
[0068] High temperature resistance test, test object: current collector prepared in Examples 1 to 6, test process:
[0069] Take A4 size samples respectively and measure the initial thickness T0;
[0070] The samples were placed in a drying oven at 220°C, 260°C and 350°C for aging tests. After different aging times, the samples were taken out and cooled to room temperature, and their thickness T1 was measured.
[0071] The shrinkage rate is calculated based on T0 and T1, and the calculation formula is: shrinkage rate = (T0-T1) / T0;
[0072] The test results are shown in Table 2.
[0073] Table 2 High temperature performance test of current collectors prepared in Examples 1 to 6
[0074]
[0075] As can be seen from Table 2, the current collector made of liquid crystal polymer non-woven fabric can withstand a high temperature of 350°C and has very good high temperature resistance. At the same time, at high temperatures, the shrinkage rate is very small and can maintain very excellent dimensional stability.
[0076] The current collectors prepared in Examples 1 to 6 were characterized in terms of surface appearance and microstructure. Since the implementation cases used non-woven fabrics with the same material and structure but different thicknesses from Kuraray Co., Ltd. of Japan, Case 1 was selected for characterization.
[0077] The observations were carried out under a high-power microscope and a scanning electron microscope. The results are shown in Figure 1 , Figure 2 , Figure 3 and Figure 4 shown.
[0078] from Figure 1 and Figure 2 It can be seen that after electroplating, the electroplated metal adheres to the surface of the fiber cloth. Figure 3 , Figure 4 It can be seen that after electroplating, copper metal is attached to the inner surface of the three-dimensional holes inside the fiber cloth.
[0079] Therefore, comprehensive Figures 1 to 4 It can be seen that after electroplating, the surface of the fiber cloth and the inner surface of the internal holes have been plated with a copper metal layer to form a continuous electroplated metal layer, realizing the metallization of the polymer fiber cloth.
[0080] Application Examples 1 to 6
[0081] Graphite, conductive agent acetylene black, thickener CMC-Na and binder SBR were mixed in a mass ratio of 95.5:1.5:1:2, deionized water was added as a solvent, and the mixture was stirred in a vacuum mixer until uniform and stable to obtain a negative electrode slurry;
[0082] The negative electrode slurry was coated on the surface of the current collector described in Examples 1 to 6, and then dried, cold pressed and cut in sequence to obtain negative electrode sheets (with a compaction density of 1.5 g / cm 3 );
[0083] According to the mass ratio of 95:2:3, NCM622 (LiNi0.6 Co 0.2 Mn 0.2 After mixing O2, binder PVDF and conductive agent acetylene black, solvent N-methylpyrrolidone (NMP) was added, and stirred in a vacuum mixer until uniform and stable to obtain positive electrode slurry; the positive electrode slurry was coated on the surface of aluminum foil, and dried, cold pressed and cut in sequence to obtain positive electrode sheets (compacted density of 3.2 g / cm 3 );
[0084] Electrolyte: The solvent is a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC) and methyl propionate (MP) in a mass ratio of 20:60:5:5:10; the electrolyte is lithium hexafluorophosphate (LiPF6), and the mass percentage of the electrolyte in the electrolyte is 12.5wt%;
[0085] Diaphragm: PP diaphragm (polypropylene diaphragm);
[0086] Assemble the positive electrode sheet, separator and negative electrode sheet polarity to obtain a battery cell; place the battery cell in a packaging shell, inject electrolyte and seal it, and sequentially perform static, compaction, formation, exhaust and sealing to obtain a lithium ion secondary battery (the negative electrode current collector of Application Example 1 adopts the current collector described in Example 1, the negative electrode current collector of Application Example 2 adopts the current collector described in Example 2, and so on, the negative electrode current collector of Application Example 6 adopts the current collector described in Example 6).
[0087] Comparative Example 1
[0088] Referring to Application Examples 1 to 6, the only difference is that the negative electrode current collector in Application Examples 1 to 6 is replaced by copper foil.
[0089] Test Case
[0090] The lithium ion batteries obtained in Application Examples 1 to 6 and Comparative Example 1 (the loading amount of the active material in the current collector is 75 g / m 2 ) to conduct battery mass energy density test, the test conditions are:
[0091] The temperature is 25℃,
[0092] Charging conditions: CCCV constant current constant voltage charging, current 0.05C, 5mV, 0.01C termination;
[0093] Discharge conditions: 0.05C continuous current discharge, terminated when the voltage drops to 2.8V;
[0094] The testing process is as follows:
[0095] 1. Fully charge the battery according to the charging conditions;
[0096] 2. Discharge at a continuous current of 0.05C. When the voltage drops to 2.8V, stop discharging.
[0097] 3. Record the discharge time t and platform voltage V;
[0098] 4. Use a thousandths balance to test the battery mass m;
[0099] Then the battery mass energy density = discharge current × discharge time × platform voltage ÷ battery mass;
[0100] The lithium ion batteries obtained in Application Examples 1 to 6 and Comparative Example 1 were subjected to a needle puncture test.
[0101] The acupuncture experiment process is as follows;
[0102] 1. Fully charge the battery according to the above charging conditions;
[0103] 2. At room temperature, in a battery puncture test machine, use a 4mm diameter steel needle to pierce the battery at a speed of 100mm / s to observe whether the battery catches fire;
[0104] The test results are shown in Table 3:
[0105] Table 3 Performance parameters of lithium ion batteries obtained from application examples 1 to 6 and comparative example 1
[0106]
[0107] It can be seen from Table 3 that the current collector of the present invention can effectively solve the safety problem caused by the high-temperature thermal shrinkage of the polymer substrate, and can also improve the mass energy density of the lithium-ion battery.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a current collector, characterized in that: The following steps are involved: A conductive metal layer is deposited on the surface and pore structure of a liquid crystal polymer modified fiber cloth substrate having a porous structure to obtain a current collector; The deposition method is as follows: a liquid crystal polymer non-woven fabric of the Vecrus series of Kuraray Co., Ltd. of Japan, with a brand name of MBBK4F-F, is plated with a layer of nickel metal on the surface of the non-woven fabric by conventional vacuum evaporation plating process, with a thickness of 0.1 μm; The liquid crystal polymer nonwoven is placed in an aqueous electroplating solution, wherein the electroplating solution contains 70 g / L copper pyrophosphate, 300 g / L potassium pyrophosphate, 15 g / L ammonium citrate and 3 ml / L ammonia water, and the pH is adjusted to about 7.5 with sulfuric acid, and electroplated at 50° C. for 1 minute, and then washed with deionized water, taken out and dried under hot pressing conditions of 75 degrees and 2 kg / square inch to obtain the current collector; Before deposition, the liquid crystal polymer modified fiber cloth substrate with a porous structure is pretreated, and the pretreatment preferably includes degreasing, roughening and activation in sequence; the activation liquid used in the activation is colloidal palladium activation liquid; the activation temperature is 23° C., and the activation time is 2 minutes; The preparation process of the colloidal palladium activation solution includes: mixing 100 mL of hydrochloric acid and 200 mL of deionized water, stirring evenly, then adding 1 g of palladium chloride and stirring, then adding 2.53 g of stannous chloride, stirring to fully react and dissolve for 12 minutes at a temperature of 32° C., to obtain a solution A; adding 75 g of stannous chloride to 200 mL of hydrochloric acid, stirring until completely dissolved, then adding 7 g of sodium stannate to prepare a white emulsion, to obtain a solution B; slowly pouring the solution B into the solution A, diluting it to 1000 mL with deionized water, to obtain the colloidal palladium activation solution; The current collector includes a liquid crystal polymer modified fiber cloth substrate with a porous structure and a conductive metal layer attached to the surface of the liquid crystal polymer modified fiber cloth substrate with a porous structure and in the pore structure; the material of the conductive metal layer includes Ni and Cu, the thickness of nickel is 0.1μm, and the thickness of copper is 1μm.
2. The preparation method according to claim 1, characterized in that The liquid crystal polymer modified fiber cloth substrate with a porous structure has a thickness of 4 to 70 μm, a porosity of 10 to 60%, a use temperature of -60 to 350° C., a tensile strength of 1 to 1500 MPa, and a pore size of 0.01 to 60 μm.
Citation Information
Patent Citations
Flexible current collector, electrode containing flexible current collector, and battery
CN106898729A
Composite current collector, battery pole piece, battery cell and lithium ion secondary battery
CN113113611A